Perancangan Aplikasi Source code library Sebagai Solusi Pembelajaran Pengembangan Perangkat Lunak - Muhammad Wali; Lukman Ahmad (KITA Institute, 2017)
Source code library reference codes on a programming language and software evaluation. Today, most Source code library for the purposes of learning software developers in the form of documentation of the use of a programming language that can be accessed through the official website developer programming languages, forum and various blogs. Because of the complexity of the features most web-based Source code library can only be accessed through the website and some others have provided documentation on each software vendor from the developers company the device. This research tries to construct a model of the application Source code library that can be used as a form of documentation for learning the use of various programming languages flexibly both in online and offline. The application allows the renewal of data/content Source code library at a time when the Internet is still available or at the time of the user's area does not have a network the Internet. In the implementation of this research will be divided in three stages, namely data collection pre development, development and implementation, and data collection of post-war development. Data collection pre development intended to get a preliminary study about the provision the core issue at hand, while the development and implementation phase focuses on model software design into diagrams and make the programming code to implement the design that has been created. While the data collection stage of the post-war development was for revamping the application made in conclusion, withdrawal, and suggestions for further research topics.